A study of post-surgical maternal morbidity and mortality in a tertiary care centre - Garg, Richa; Desai, Ranjana (International Journal of Research in Medical Sciences, 2017)
Background: Surgery is a lifesaving procedure. With the advances in anaesthetic services and improved surgical techniques the morbidity and mortality of this have come down considerably. Amongst all surgeries Caesarean section is most commonly performed major surgery. The study was aimed to evaluate the post-surgical maternal deaths and to examine etiology and preventability of maternal deaths and make protocol for decreasing future mortality in a series of 46102 deliveries between 2014 to 2016 Methods: This was a prospective analytical study of all post-surgical maternal deaths at Umaid Hospital Dr. S. N. Medical College Jodhpur, Rajasthan, India between July 2014 and June 2016. Results: The total number of deliveries in 2 years (July 2014-June 2016) was 46102 and number of maternal deaths was 98. Out of this 49(50%) were post-surgical deaths. Majority of patients 57.14% were between age group of 21-30 years and 14.28% were below 20 years. Majority of patients were rural 77.55% and 22.4 belonged to urban area. 22.4 % were multigravidae and 46.9% were primigravidae. 89.7% of patients were unbooked. 20% deaths occurred within 4hrs after surgery, 53% deaths within 4-12 hrs, 8.16% deaths between 12-24 hours. Caesarean was done in (40.8%) cases. In 32% cases hysterectomy was done for postpartum haemorrhage. In one case, re-exploratory laparotomy was done. All the patients were associated with risk factors and lack of proper antenatal care, lack of knowledge, illiteracy, poor transport and late referral further increases the surgical risk. Conclusions: Good antenatal care, high risk screening, comprehensive emergency obstetric services, hospital delivery and incorporation of obstetric drills decreases the post-surgical deaths.